Self-Amplifying Assembly of Peptides in Macrophages for Enhanced Inflammatory Treatment - Song, Yanqiu; Li, Mingming; Song, Na; Liu, Xin; Wu, Guangyao; Zhou, Hao; Long, Jiafu; Shi, Linqi; Yu, Zhilin (Journal of the American Chemical Society, 2022)
Enzyme-regulated in situ self-assembly of peptides represents one versatile strategy in the creation of theranostic agents, which, however, is limited by the strong dependence on enzyme overexpression. Herein, we reported the self-amplifying assembly of peptides precisely in macrophages associated with enzyme expression for improving the anti-inflammatory efficacy of conventional drugs. The self-amplifying assembling system was created via coassembling an enzyme-responsive peptide with its derivative functionalized with a protein ligand. Reduction of the peptides by the enzyme NAD(P)H quinone dehydrogenase 1 (NQO1) led to the formation of nanofibers with high affinity to the protein, thereby facilitating NQO1 expression. The improved NQO1 level conversely promoted the assembly of the peptides into nanofibers, thus establishing an amplifying relationship between the peptide assembly and the NQO1 expression in macrophages. Utilization of the amplifying assembling system as vehicles for drug dexamethasone allowed for its passive targeting delivery to acute injured lungs. Both in vitro and in vivo studies confirmed the capability of the self-amplifying assembling system to enhance the anti-inflammatory efficacy of dexamethasone via simultaneous alleviation of the reactive oxygen species side effect and downregulation of proinflammatory cytokines. Our findings demonstrate the manipulation of the assembly of peptides in living cells with a regular enzyme level via a self-amplification process, thus providing a unique strategy for the creation of supramolecular theranostic agents in living cells.